2016
DOI: 10.1038/gim.2015.219
|View full text |Cite
|
Sign up to set email alerts
|

Taking advantage of an old concept, “illegitimate transcription”, for a proposed novel method of genetic diagnosis of McArdle disease

Abstract: We propose considering the use of PBMCs for detecting mutations that are thought to cause McArdle disease, particularly for studying their actual pathogenicity.Genet Med 18 11, 1128-1135.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
(44 reference statements)
0
10
0
1
Order By: Relevance
“…Missense mutations were also prevalent (55% of patients), and included the two other more frequent PYGM mutations in the Spanish population, c.2392T > C (p.W798R) and c.613G > A (p.G205S), and the non‐synonymous variants c.280C > T (p.R94W), c.347T > C (p.L116P), c.521G > A (p.G174D), c.1094C > T (p.A365V), c.1147G > A (p.E383K), c.1366G > A (p.V456M), c.1979C > A (p.A660D), and c.2111C > T (p.A704V). Four frameshift PTC c.13_14delCT (p.L5Vfs*22), c.2262delA (p.K754Nfs*49), c.2310_2311dupCC (p.R771Pfs*33), c.1470dupG (p.R491AfsX7) and four splice‐disrupting mutations c.645G > A, c.1827 G > A, c.1093‐1G > T (Bruno et al., ) and c.244‐3_244‐2CA) (Fernandez‐Cadenas et al., ; Garcia‐Consuegra et al., ) were also identified. All these variants have been deposited in the Leiden Open Variation Database, and can be found in the following link: https://databases.lovd.nl/shared/variants/PYGM?search_var_status=%3D%22Marked%22%7C%3D%22Public%22.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Missense mutations were also prevalent (55% of patients), and included the two other more frequent PYGM mutations in the Spanish population, c.2392T > C (p.W798R) and c.613G > A (p.G205S), and the non‐synonymous variants c.280C > T (p.R94W), c.347T > C (p.L116P), c.521G > A (p.G174D), c.1094C > T (p.A365V), c.1147G > A (p.E383K), c.1366G > A (p.V456M), c.1979C > A (p.A660D), and c.2111C > T (p.A704V). Four frameshift PTC c.13_14delCT (p.L5Vfs*22), c.2262delA (p.K754Nfs*49), c.2310_2311dupCC (p.R771Pfs*33), c.1470dupG (p.R491AfsX7) and four splice‐disrupting mutations c.645G > A, c.1827 G > A, c.1093‐1G > T (Bruno et al., ) and c.244‐3_244‐2CA) (Fernandez‐Cadenas et al., ; Garcia‐Consuegra et al., ) were also identified. All these variants have been deposited in the Leiden Open Variation Database, and can be found in the following link: https://databases.lovd.nl/shared/variants/PYGM?search_var_status=%3D%22Marked%22%7C%3D%22Public%22.…”
Section: Resultsmentioning
confidence: 99%
“…Myoblasts were isolated from biopsies of P40 and a control subject by explant culture (Askanas & Gallez‐Hawkins, ). Retrotranscription was done using the SuperScript III First‐Strand Synthesis System (Invitrogen, Carlsbad, CA), and amplification of the cDNA corresponding to the PYGM gene (NM_005609.2) was performed in two fragments as previously reported (Garcia‐Consuegra et al., ). One microliter of amplified PYGM cDNA encompassing the position of the mutation c.2310_2311dupCC (p.R771Pfs*33) was analyzed on the Agilent 2100 Bioanalyzer in combination with microfluidic DNA‐1000 chips (Agilent Technologies, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although an effort was made to pursue RT-PCR PYGM -mRNA experiments from the family trio affected by the novel SD mutation, the analysis was not successful. And, no protein and functional studies were performed for the novel SD and SR1 mutations, however, future studies are planned to further investigate their effects [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Besides the invasive nature of the muscle biopsy procedure, the usefulness of analyzing cDNA synthesized from tissuespecific transcripts is limited by a cellular homeostatic mechanism known as 'nonsense mediated mRNA decay' (NMD), which eliminates aberrant transcripts that contain nonsense and frameshift mutations [23,[26][27][28][29]. A study of 28 GSDV patients found that NMD was important [30].…”
Section: Pathological and Molecular Changes In Gsdvmentioning
confidence: 99%